Evaluasi Pemajakan Terhadap Penyelenggara Sistem Elektronik Transaksi Digital yang Berasal dari Luar Negeri - Maya Mahatma Putri; Yulianti Abbas (Owner : Riset dan Jurnal Akuntansi, 2023)
Cross-border trade brings new digital taxation issues in Indonesia. There are several tax treatment for foreign electronic sistem operators for trading through the electronic sistem in Indonesia. This study aims to evaluate the implementation of taxation of foreign electronic sistem operators based on the "Four Maxims" principle. This study uses a case study approach and collects data  from interview with tax authorities, the tax consultants from multinational company, and academics. The results of the study show that for Value Added Taxes, there is no need to look at the substance of Permanent Establishment since the current rule applies equally to all Value Added Tax collectors conducting  trade through the Electronic Sistem (PMSE). As for Income Taxes, only those identified as Permanent Establishment is taxable as Domestic Taxpayers. Therefore, for Value Added Taxes, the Principles of Equality and Convenience have been fulfilled, although the principles of legal certainty and efficiency in collections have yet to be fulfilled. As for Income Taxes, the results of this study show that all respondens agreed that the level playing field have yet to be reached..